Further development of a reverse‐transcription loop‐mediated isothermal amplification (RT‐LAMP) assay for the detection of foot‐and‐mouth disease virus and validation in the field with use of an internal positive control. Issue 6 (6th May 2020) - Bath, Carolyn; Scott, Megan; Sharma, Puspa Maya; Gurung, Ratna B.; Phuentshok, Yoenten; Pefanis, Stephen; Colling, Axel; Singanallur Balasubramanian, Nagendrakumar; Firestone, Simon M.; Ungvanijban, Sahawatchara; Ratthanophart, Jadsada; Allen, John; et al.
Abstract: Foot‐and‐mouth disease (FMD) is a highly contagious viral disease of cloven‐hooved animals. Global outbreaks have highlighted the significant economic, trade, psychosocial and animal welfare impacts that can arise from the detection of disease in previously 'FMD‐free' countries. Rapid and early diagnosis provides significant advantages in disease control and minimization of deleterious consequences. We describe the process of further development and validation of a reverse‐transcription loop‐mediated isothermal amplification foot‐and‐mouth disease virus (RT‐LAMP‐FMDV) test, using a published LAMP primer set, for use in the field. An internal positive control (IPC) was designed and introduced for use with the assay to mitigate any intrinsic interference from the unextracted field samples and avoid false negatives. Further modifications were included to improve the speed and operability of the test, for use by non‐laboratory trained staff operating under field conditions, with shelf‐stable reaction kits which require a minimum of liquid handling skills. Comparison of the assay performance with an established laboratory‐based real‐time reverse transcriptase PCR (rRT‐PCR) test targeting the 3D region of FMD virus (Tetracore Inc) was investigated. LAMP has the potential to complement current laboratory diagnostics, such as rRT‐PCR, as a preliminary tool in the investigation of FMD. We describe a strategic approach to validation of the test for use in the field using extracted RNA samples of various serotypes from Thailand and then finally unextracted field samples collected from FMD‐suspected animals (primarily oral lesion swabs) from Bhutan and Australia. The statistical approach to validation was performed by Frequentist and Bayesian latent class methods, which both confirmed this new RT‐LAMP‐FMDV test as fit‐for‐purpose as a herd diagnostic tool with diagnostic specificity >99% and sensitivity 79% (95% Bayesian credible interval: 65, 90%) on unextracted field samples (oral swabs).